Assessment of migrated foreign bodies in the maxillae by x-ray fluorescence spectrometry - Matsuda, Shinpei; Ohba, Seigo; Yoshimura, Hitoshi; Kobayashi, Junichi; Watanabe, Ikuya; Sano, Kazuo (The Journal of craniofacial surgery, 2014)
Two cases of foreign bodies that were incidentally observed on orthopantomographs are reported in this study. The foreign bodies were analyzed using an x-ray fluorescence spectrometer to identify what the migrated foreign bodies were and what migration pathways they had taken. The removed metallic foreign bodies from the maxillae of 2 patients, who were referred to the Department of Dentistry and Oral Surgery of the University of Fukui Hospital, were analyzed using an x-ray fluorescence spectrometer in the Department of Dental and Biomedical Materials Science, Nagasaki University. The major component of foreign body in patient 1 was silver, and that in case 2 was iron. On the basis of the imaging results and the patients' clinical history, the foreign bodies were considered to be caused by iatrogenic migration. Understanding the existence of foreign bodies and their migration pathway into the jaw bone can thus make clinicians more aware of such migrations and can thereby contribute to reducing iatrogenic accidents.